2021
DOI: 10.3390/nu13020695
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variations Involved in the Inter-Individual Variability of Circulating Cholesterol Concentrations in Response to Diets: A Narrative Review of Recent Evidence

Abstract: The number of nutrigenetic studies dedicated to the identification of single nucleotide polymorphisms (SNPs) modulating blood lipid profiles in response to dietary interventions has increased considerably over the last decade. However, the robustness of the evidence-based science supporting the area remains to be evaluated. The objective of this review was to present recent findings concerning the effects of interactions between SNPs in genes involved in cholesterol metabolism and transport, and dietary intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…The CYP2C9 variants are worth investigating since this member of the cytochrome P450 family has a major role in the metabolism of most statins and has more than 60 reported genetic variants [ 35 ]. Moreover, we observed in both cohorts an association between higher HDL-C and the minor alleles of rs1532624 and rs708272 SNPs of CETP, a protein involved in the transfer of cholesteryl esters from HDL-C to other lipoproteins [ 36 ], confirming the results of several studies performed on a multitude of different ethnicities [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The CYP2C9 variants are worth investigating since this member of the cytochrome P450 family has a major role in the metabolism of most statins and has more than 60 reported genetic variants [ 35 ]. Moreover, we observed in both cohorts an association between higher HDL-C and the minor alleles of rs1532624 and rs708272 SNPs of CETP, a protein involved in the transfer of cholesteryl esters from HDL-C to other lipoproteins [ 36 ], confirming the results of several studies performed on a multitude of different ethnicities [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, APOE4 carriers, despite their sensitivity to omega-3 deficiencies, may not always benefit from fish oil supplementation. Furthermore, Abdullah et al (2021), after reviewing the available literature, have recently shown APOE to be among the genes involved in the inter-individual variability of circulating cholesterol concentrations in response to diet (Abdullah et al 2021). Some more evidence of the impact of APOE genotype status on the response to diet comes from transgenic targeted gene replacement mice.…”
Section: Apoe Longevity and Dietmentioning
confidence: 99%
“…Genome wide association studies (GWAS) have paved the way for identification of Single nucleotide polymorphisms (SNPs) as drivers of cardiometabolic diseases. Therefore, SNPs have been known as a proper choice to identify phenotypic differences and address inter-individual variability [ 14 ]. In this regard, it is of great importance to identify SNP in the fatty acid desaturase (FADS) genes and determine their interaction with environmental factors such as diet in relation to risk of metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%